PENGARUH CORPORATE GOVERNANCE, LEVERAGE, UKURAN PERUSAHAAN, DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Sektor Pertambangan Non Migas yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Ziqra Reza; Zirman Zirman; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of corporate governance, leverage, company size, and disclousure ofcorporate social responsibilityagainst tax avoidance. The dependent variable used in this research was the practice of tax avoidance proxied by the effective tax rate (ETR), while the independent variable was institutional ownership, independent commissioner, the audit committe, leverage, company size and corporate social responsibility (CSR). The sample used in this study were mining companies non oil and gas listed in Indonesia Stock Exchange for period of 2013-2016 is based on criteria that have been set. The sampling method used is purposive sampling and testing this hypothesis using multiple linear regression analysis. The result of this study showed that independent commisioner, leverage and size company have significant effect on tax avoidance, but the variable institutional ownership, audit commite and CSR did not affect on tax avoidance.Keyword : Tax avoidance, ETR, Corporate Governance, Institutional Ownership, Idependent Commissioner, Audit Commite, Leverage, Company Size, CSR